"A dignidade suprema de um navio perdendo a rota": figurações de um Leminski acéfalo - Pereira, Eduardo Silva (2018)
This research seeks to demonstrate a kind of reading of poetry as a historic, politic and non literary cipher. Questioning the integrity of literature as a stiffened institution, as well as poetry in it's self coincidence. Throught a montage's metodology and a distribution in a atlas form, esthetic documents envolving Leminski antes his production's period, as well as documents from movements in that time, descontextualizing it's habitual positions and seting them in game using differents ways of connection. Also, this paper objectives identifying a way of reading kamiquase poem, to, from it, atest a way of reading poetry, literature, arts and politics inconsitents and not self coincidents. Lastly, possible reading way of kamiquase poem, tha make this objectives possibles, is the way of reading poetry reassembled in a acephalic way, with capital - in a center of comand and birthplace of logic therms - dismissed, reading poetry in a non logical way.